FDI and wages: Evidence from firm-level and linked employer-employee data in Hungary, 1986 - 2008 - John S. Earle; Álmos Telegdy; Gábor Antal (Institute for the Study of Labor (IZA), 2012)
We estimate the wage effects of foreign direct investment (FDI) with universal firm-level and linked employer-employee panel data containing 4,926 foreign acquisitions in Hungary. Matching on pre-acquisition data and controlling for fixed effects for firms and detailed worker groups, we find 12-28 percent effects on average wages. The wage effect mostly reverses for 983 foreign acquisitions later divested to domestic owners. We find positive effects for all worker types, occupations, and wage quantiles. The evidence implies little role for either measurement problems or residual selection, but suggests a strong cross-firm association of FDI wage premia with similar differentials in productivity.
Keywords: F23; F66; J31; 330; foreign acquisitions; FDI; earnings; wage differentials; productivity; difference-in-differences matching; employer effects; Hungary; Lohn; Direktinvestition; Ausländisch; Übernahme; Lohnstruktur; Produktivität; Schätzung; Ungarn